2020
DOI: 10.3390/catal10091072
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Structure of Fatty Acid Photodecarboxylases and Glucose-Methanol-Choline Oxidoreductases

Abstract: Glucose-methanol-choline (GMC) oxidoreductases are a large and diverse family of flavin-binding enzymes found in all kingdoms of life. Recently, a new related family of proteins has been discovered in algae named fatty acid photodecarboxylases (FAPs). These enzymes use the energy of light to convert fatty acids to the corresponding Cn-1 alkanes or alkenes, and hold great potential for biotechnological application. In this work, we aimed at uncovering the natural diversity of FAPs and their relations with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 124 publications
(120 reference statements)
0
19
0
Order By: Relevance
“…Figure 2 visually illustrates how ANC1 and ANC2 are more similar to WT (more black bars) whereas ANC3 has a lower sequence identity (more white bars). Despite the differences, they all share the conserved amino acid positions that characterize FAPs: C432, R451 and A576 (numbering corresponding to CvFAP) [29,30] . A576 is possibly one of the most striking difference between FAPs and other members of the GMC superfamily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 visually illustrates how ANC1 and ANC2 are more similar to WT (more black bars) whereas ANC3 has a lower sequence identity (more white bars). Despite the differences, they all share the conserved amino acid positions that characterize FAPs: C432, R451 and A576 (numbering corresponding to CvFAP) [29,30] . A576 is possibly one of the most striking difference between FAPs and other members of the GMC superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…A576 is possibly one of the most striking difference between FAPs and other members of the GMC superfamily. At this position, most members of the GMC superfamily have a histidine [30] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most highly enriched molecular functions of the 6 screened genes were nicotinamide adenine dinucleotide (NAD) binding, oxidoreductase activity and fatty acid activity ( Figure 6A ). The involvement of these molecular functions in fatty acid metabolism has been previously reported [ 14 , 15 ]. Moreover, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis suggested that the 6 genes might participate in pathways related to fatty acids ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 97%